WEIGHTED GENE CO-EXPRESSION NETWORK ANALYSIS IDENTIFIES BIOLOGICAL PATHWAYS AND BIOMARKER GENES ASSOCIATED WITH CHICKENS' ADAPTATION TO BOTH LOW AND HIGH ALTITUDES - Pshtiwan S.A. Bebane; Paiman Yousif; Sarbast I. Mustafa; Sami mamand (Science Journal of University of Zakho)
The main aim of the study was to identify modules, hub genes, and possible pathways linked with hypoxia adaptation in six types of tissues and organs (heart, kidney, liver, lung, muscle, and spleen) at altitudes ranging from 2,300 to 3,500 metersOn a transcription dataset from hypoxia-sensitive tissues, we performed weighted gene co-expression network analysis on 13,940 selected genes, and 10 transcriptional modules in total were detected (Turquoise 196 genes, Purple 27 genes, Blue 196, Brown 182, Yellow 108, Green 79 genes, Red 69 genes, Black 50 genes, Pink 44 genes, and Magenta 37 genes). Furthermore, we discovered that the majority of variable genes were screened by sub-setting 1000 genes; samples belonging to the same tissue clearly clustered together, and the expression in the liver and lung was more associated than in the heart and spleen. Functional enrichment analysis of all genes in 12 selected modules revealed that 9 KEGG pathways were considerably enriched, 13 Gene ontology terms were significantly enriched in the biological process and cellular component pathways, and 15 gene ontology terms were significantly enriched in the molecular function pathway. Through weighted gene co-expression network analysis, the results of this study expand our knowledge of the molecular pathway of catalytic and metabolic activity as a biomarker pathway